Identification of microRNAs with a role in glucose stimulated insulin secretion by expression profiling of MIN6 cells. - O'DRISCOLL, LORRAINE (My University, 2010)
MicroRNAs (miRNAs) are a family of endogenous small non-coding RNAs which regulate mRNAs at the post-transcriptional level. MiRNAs have been identified in both normal physiological and pathological conditions. To date, a limited number of miRNAs have been shown to be involved in the regulation of insulin secretion. We have identified a panel of 10 miRNAs down-regulated in glucose non-responsive MIN6 cells compared to glucose responsive cells using TaqMan Low Density human microRNA arrays. Of these 10 miRNA targets, subsequent functional investigations involving knockdown of mir-200a, mir-130a and mir-410 levels suggested that they may decrease the capability of MIN6 cells to secrete insulin in response to stimulatory levels of glucose. Conversely, experiment with over-expression of mir-410 suggest that it may enhance levels of glucose stimulated insulin secretion. In this study, we have also identified 21 miRNAs not previously known to have a potential murine homolog.
PUBLISHED
Keywords: microRNA; GSIS; insulin secretion; MIN6; Genes & Society